Analisis Pemikiran Politik Islam Al-Syaibani: Landasan Teoritis dan Implikasinya dalam Kebijakan Publik - Syera Saffina; Azmia Siti Munasifah; Adam Adam; Lina Marlina (STIKes Ibnu Sina Ajibarang, 2025)
Muhammad bin Al-Hasan Al-Syaibani (132-189 H/749-805 AD) was a leading fiqh expert and main student ofImam Abu Hanifah who played an important role in the development of the Hanafi School.Born in Wasith, Iraq, Al-Syaibani studied from great scholars such as Abu Hanifah, Abu Yusuf, Imam Malik, and Sufyan ats-Tsauri, combining the traditions ofahl al-ra'yi (Iraq) and ahl al-hadith (Medina).His works, such as Zhahir al-Riwayah (including Al-Jami' al-Kabir and Al-Siyar al-Kabir) and Al-Nawadir, have become major references in Hanafi jurisprudence. Al-Syaibani's political thought emphasizes the concept of a sharia-based state, social justice and accountable leadership. He divided the economic system into four sectors (agriculture, commerce, industry, and rent) with a focus on collective welfare. In international law (Al-Siyar al-Kabir), he formulated principles of relations between Muslims and non-Muslims, ethics of war, and diplomacy that have been influential until the modern era. This study analyzes the relevance of his thoughts in contemporary contexts, including Islamic economics, social justice, and international law, as well as the challenges in adapting his ideas amidst globalization. Al-Shaibani's thoughts offer an integrative framework between spirituality, morality, and governance practices,making them relevant to contemporary discussions of Islamic politics and economics.